Evaluation of an Online Teaching Model for Academic English Writing: Insights from Chinese EFL College Teachers - Gui, Mingxian; Siraj , Saedah Binti; Razak , Rafiza Binti Abdui (Journal of Ecohumanism, 2025)
This study addresses the challenges faced by Chinese EFL (English as a Foreign Language) college students in academic English writing, specifically the need for effective and accessible online teaching models. The research explores the feasibility and effectiveness of a newly designed online academic writing model aimed at improving students’ writing skills. A mixed-methods approach was employed, using questionnaires and semi-structured interviews with TEFL teachers to collect data. The findings show that the model is well-received by both teachers and students, with notable improvements in writing performance, cultural relevance, technology integration, and accessibility. However, the study also identifies challenges, such as the limitations of AI-supported feedback and the need for better collaborative learning activities. The research concludes that the model holds promise for enhancing academic writing instruction, providing a foundation for future improvements and offering implications for designing effective online language learning tools tailored to Chinese EFL learners.